Relicts of Rheic Ocean in Southwest Iberia (Ossa-Morena Zone - Portugal) - Pedro, Jorge (2010)
The geodynamic evolution of Iberian Peninsula during the Variscan Orogeny is directly related with the Wilson Cycle of Rheic Ocean (Vera, 2004; Dias et al., 2006; Ribeiro et al., 2007). This relationship is underlined by major sutures zones and by several occurrences of high pressure metamorphic rocks (i. e. eclogites and blueschits) and ophiolites terranes (scattered slices) in the Iberian Terrane. The Ossa-Morena Zone (OMZ), the southernmost unit of the Iberian Autochthon Terrane in SW Iberia (Fig. 1), is bounded by two major tectonic lines: the Northern boundary which corresponds to the Tomar-Badajoz-Cordoba Shear Zone (TBCSZ), a Cadomian suture reworked in transpression during the Variscan Orogeny, and the Southern boundary, which corresponds to the South Iberian Variscan Suture Zone (Ribeiro et al., 2007). In the OMZ the Proterozoic basement is separate from the lower Cambrian rocks (felsic volcanics and conglomerates) by a major unconformity that corresponds to the beginning of the Variscan Cycle. The rifting stage is marked by the deposition of lower Cambrian limestones and by bimodal extensional magmatism (Mata & Munhá, 1990). The lower Palaeozoic sequence of OMZ shows strong variations of facies, corresponding to the existence of several local sedimentary basins. This feature is related with a near continuous extensional tectonics regime (Rheic opening), until Silurian times. The Silurian sequence denotes a deep sedimentary environment. At this time, Rheic becomes a wide ocean and the passive margin evolution during lower Palaeozoic is confirmed by the sedimentary record and magmatism chemistry (Mata & Munhá, 1990, Ribeiro et al, 1992; 1997). During lower Devonian the sedimentary record show the existence of tectonic instabilities probably related with the beginning of the Rheic oblique closure. This assumption is supported by the existence of (1) local flysch deposits with lower Devonian age, (2) the occurrence of reworked slices of Silurian rocks within lower Devonian formations and (3) the presence of a Tectonic Accretionary Complex which truncates the autochthonous sequence of OMZ, ranging from Precambrian to upper Silurian/Lower Devonian (Araújo et al, 2005; 2006). During middle to upper Devonian occurs the main tectono-metamorphic event related with the Rheic closure in the southern border of OMZ (Quesada et al., 1994; Fonseca et al., 1999): a subduction/obduction process, with northwards polarity, is responsible by the generation of a flake like geometry and by the occurrence of the Tectonic Accretionary Complex, related with the obduction in the Southern Iberia Variscan Suture, which includes slices of (1) autochthonous rocks, (2) ophiolites and (3) high-pressure rocks (blueschists and eclogites). Also related with the subduction/obduction process occurs the emplacement of the Paired Ophiolite Belt. This ophiolite belt is formed by the Beja-Acebuches Ophiolite Complex (BAOC), an external ophiolite that mark the South Iberian Variscan Suture Zone, and by the Internal Ophiolite Sequence (IOS) (Fonseca, 1995; Pedro, 2004; Ribeiro, 2006; Ribeiro et al., 2007) Also in Devonian times the orogenic magmatism starts with the emplacement of the first rocks of Beja Massif and goes on until upper Carboniferous with the emplacement of widespread intrusive rocks.